Evaluation of hepatoprotective effect of chloroform and methanol extracts of Opuntia monacantha in paracetamol-induced hepatotoxicity in rabbits (Bangladesh Journal of Pharmacology, 2015)
The chloroform and methanol extracts of Opuntia monacantha were studied for its hepatoprotective effect against paracetamol induced liver damage in rabbits. Results proved that both extracts at 200, 400 and 600 mg/kg body weight in one week protocol showed significant (p